Analysis of Thermal Characteristics of Batch Cooling Sonocrystallization: Effect on Crystal Attributes. Issue 3 (19th December 2022) - Yadav, Jyoti; Srivastava, Abhishek; Patel, Swati A.
Abstract: The control of desired product quality attributes in the crystallization process is one of the major concerns of the pharmaceutical industries due to the established standard limits for active pharmaceutical ingredients in applications. The objective of the present work is to establish the fundamental understanding and methodology of the batch cooling sonocrystallization process to tune the crystal attributes over the range of operating parameters, i.e., ultrasound amplitude, duration of sonication, and cooling rate. For the constant cooling rate, the effect of three levels of ultrasound amplitude has been investigated over the range of durations of insonation. It is observed for a fixed cooling rate that the optimized set of ultrasound parameters shortens the induction time resulting in a finer range of particles increasing the surface area and narrowing the particle size distribution. The performance of the process in terms of thermal characteristics has been analyzed to delineate the effect of operating parameters to be employed as a function of the product characteristics. The simple expressions for temperature profiles during the process have been proposed as a function of saturation temperature to facilitate their applications in the optimization of the operating parameters for the desired product size and size range. Abstract : Tuning the operating parameters of ultrasound‐assisted crystallization—amplitude of power (%) and duration of insonation—results in fine crystal products with narrow size distribution where temperature plays a crucial role.